THE URGENCY OF REGULATING THE AUTHORITY OF THE INDONESIAN NATIONAL ARMED FORCES (TNI) IN COUNTERING TERRORISM THAT THREATENS THE SOVEREIGNTY OF THE UNITARY REPUBLIC OF INDONESIA - Eka Yudha Kurniawan; Dhiana Puspitawati; Milda Istiqomah (RADJA PUBLIKA, 2023)
The authority of the Indonesian National Armed Forces (TNI) in addressing acts of terrorism, as mandated by the TNI Law through Non-War Military Operations (OMSP), as stated in Article 7 paragraph (2) letter (b) number 3 of Law Number 34 Year 2004 regarding the Indonesian National Armed Forces, is one of the main tasks of the TNI in OMSP, hence it is the mandate of the TNI's authority in addressing acts of terrorism. To date, there are no implementing regulations that govern this TNI authority, resulting in ambiguity and a legal vacuum that causes hesitation in every military operation carried out by the TNI to counteract acts of terrorism, significantly threatening state sovereignty, thus raises questions with the problems: 1. What is the urgency of the regulation of authority in countering terrorism that threatens the sovereignty of the Indonesian State by the Indonesian National Armed Forces (TNI); 2. What is the model of involvement of the Indonesian National Armed Forces (TNI) in countering acts of terrorism that threaten the sovereignty of the Indonesian State? Therefore, the author uses normative legal research, a statutory approach method, a concept analysis, and a comparison approach. With this research, the author tries to explain that the arrangement of TNI authority in addressing acts of terrorism that have threatened state sovereignty is essential and urgent to be immediately enacted as the legality of the military operation carried out considering the current threat of terrorism which is increasingly developing following the times. So that the involvement of the TNI in addressing acts of terrorism is no longer carried out as an auxiliary task to the Indonesian National Police (POLRI). The TNI, in addressing acts of terrorism threatening state sovereignty, has clear and firm boundaries by the place, time, and level of threat such that the TNI can directly conduct military operations to address these acts of terror.